What mother won't tell me - Menger, Ivar Leon (Poisoned Pen Press, 2024)
"Deep in the forests of Nordland, in a lake-side cabin on a small island, Juno has lived in almost complete isolation since early childhood. She has only her Mama and Papa and her little brother Boy for company. They live in constant fear. For danger could already be lurking on the other side of the lake, seeking them out - Strangers, as they call them, who want to take revenge on their father and destroy the family. But Mama and Papa are wise and careful, they have taken every possible precaution: digging out a secret shelter, preparing emergency pills in case they're attacked, and making the children live by seven strict commandments. All so Juno and Boy feel protected and safe. For now. Until everything changes. Juno is young and restless, and when she's spotted by a Stranger she sets in motion a chain of frightening events. In an increasingly threatening new reality, Juno starts to suspect that more than a few secrets have been kept from her. She doesn't know her parents at all, and she doesn't know herself. But whoever Mama and Papa are, they'll do anything to keep Juno to themselves"--